PP2A interacts with KATANIN to promote microtubule organization and conical cell morphogenesis. Issue 8 (13th June 2022) - Ren, Huibo; Rao, Jinqiu; Tang, Min; Li, Yaxing; Dang, Xie; Lin, Deshu
Abstract: The organization of the microtubule cytoskeleton is critical for cell and organ morphogenesis. The evolutionarily conserved microtubule‐severing enzyme KATANIN plays critical roles in microtubule organization in the plant and animal kingdoms. We previously used conical cell of Arabidopsis thaliana petals as a model system to investigate cortical microtubule organization and cell morphogenesis and determined that KATANIN promotes the formation of circumferential cortical microtubule arrays in conical cells. Here, we demonstrate that the conserved protein phosphatase PP2A interacts with and dephosphorylates KATANIN to promote the formation of circumferential cortical microtubule arrays in conical cells. KATANIN undergoes cycles of phosphorylation and dephosphorylation. Using co‐immunoprecipitation coupled with mass spectrometry, we identified PP2A subunits as KATANIN‐interacting proteins. Further biochemical studies showed that PP2A interacts with and dephosphorylates KATANIN to stabilize its cellular abundance. Similar to the katanin mutant, mutants for genes encoding PP2A subunits showed disordered cortical microtubule arrays and defective conical cell shape. Taken together, these findings identify PP2A as a regulator of conical cell shape and suggest that PP2A mediates KATANIN phospho‐regulation during plant cell morphogenesis. Abstract : Conical cells that protrude from the petal epidermis represent a striking example of a specialized cell shape. The conserved protein phosphatase PP2A interacts with and dephosphorylates KATANIN to cooperatively regulate cortical microtubule organization during Arabidopsis conical cell morphogenesis.